MODEL REKRUTMEN CALON ANGGOTA LEGISLATIF PARTAI GOLONGAN KARYA KABUPATEN BANDUNG PADA PEMILIHAN UMUM TAHUN 2014 - Budi Kurniadi (Scientia Regendi, 2020)
Selection of candidates for parliamentarians who have the ability, knowledge and competence are determined through political party policy. The Regional Leadership Council of the Bandung-based Golongan Karya Party is still faced with a crucial problem that can affect the existence and greatness of the party. The purpose of this study is to describe deeply the political recruitment model. The recruitment model of the legislative candidate for the Regional Leadership Council of the Group of Work in Bandung Regency is a mixture of open and closed which is still colored by the dominance of political interests, especially in the placement of serial numbers. In general, the recruitment process refers to party policy, although the subjective aspect is still visible in candidates who have potential from outside the cadre, and the selection team is considered to be not independent because it is part of the nominating people who close the opportunity for party cadres. This attitude is considered a discriminatory attitude that can affect the solidity and existence of political parties to get candidates from the best cadres.